An Andean-type arc system in Rodinia constrained by the Neoproterozoic Shimian ophiolite in South China - Zhao, Jun-Hong; Asimow, Paul D.; Zhou, Mei-Fu; Zhang, Jian; Yan, Dan-Ping; Zheng, Jian-Ping (Precambrian research, 2017)
•The 800-Ma Shimian mafic-ultramafic mélange is an SSZ-type ophiolite.•South China was not located in the centre of Rodinia.•A giant Andean-type arc system existed along the NW margin of Rodinia. The configuration of the supercontinent Rodinia has long been a matter of debate; the key controversy is the position of South China in Rodinia. We report an incomplete Neoproterozoic ophiolite sequence, including gabbros and serpentinized peridotites intruded by mafic dikes, near Shimian (Sichuan Province), along the western margin of the Yangtze Block in South China. Serpentinized peridotites have very low REE (0.14–1.16ppm) and trace element concentrations, and are interpreted as parts of a depleted mantle sequence. Chromites from the serpentinized peridotites have low TiO2 (<0.3wt%) and Fe2O3 (<7.6wt%), and moderate Cr/(Cr+Al) (0.48–0.67) and Mg/(Mg+Fe2+) (0.42–0.67) ratios and are clearly indicative of strong depletion of the host peridotites, similar to those of supra-subduction zone (SSZ). Mafic dikes and gabbros contain zircon grains with similar U-Pb ages of ∼800Ma, and are chemically akin to MORB-like tholeiitic basalts and boninite-series volcanic rocks reported in other SSZ ophiolites and in the Izu-Bonin-Mariana arc system. Therefore, the serpentinized peridotite, mafic dikes and gabbros together appear to form a SSZ-type ophiolite assemblage preserving the accretion of oceanic lithosphere to the western Yangtze Block. The age and location of the Shimian ophiolite rule out the possibility that South China was located in the centre of Rodinia. Instead, the Neoproterozoic arc-affinity igneous rocks at the western margin of the Yangtze Block are well correlated with those in Greater India and Madagascar. These three blocks thus together formed a giant Andean-type arc system along the NW margin of Rodinia that existed for more than 100Mys.